Lactobacillus acidophilus impairs the establishment of pathogens in a subgingival multispecies biofilm - Bueno, Manuela Rocha; Dudu-Silva, Gustavo; Macedo, Tatiane Tiemi; Gomes, Aline Paim de Abreu Paulo; Rodrigues Oliveira Braga, Arthur; Aguiar Silva, Lucas Daylor; Bueno-Silva, Bruno (Frontiers in Dental Medicine, 2023)
The present study evaluated the anti-biofilm effects of Lactobacillus acidophilus within a subgingival multispecies biofilm. Lactobacillus acidophilus (LaA5) at 1x10 2 , 1x10 4 and 1x 10 6 were included in the beginning of biofilm formation, which lasted 7 days. The biofilms were comprised of 33 periodontitis-related bacterial species and the Calgary Biofilm device was used. At the end, DNA-DNA hybridization (checkerboard) was performed. Kruskal-Wallis followed by Dunn post-hoc were performed (p≤0.05). LaA5 at 1x10 4 and 1x10 6 reduced the total counts of biofilm and the proportions of red and green complexes when compared to the control biofilm without LaA5 (p≤0.05). LaA5 at 1x10 4 increased proportions of Actinomyces complex compared to control (p≤0.05). Both LaA5 at 1x10 4 and 1x 10 6 respectively decreased levels of 20 and 14 distinct species, including P. gingivalis, P. intermedia, F. nucleatum polymorphum and P. micra compared to control (p ≤ 0.05). Only LaA5 at 1x10 4 reduced levels of T. forsythia, F. periodonticum and A. actinomycetencomytans compared to control (p ≤ 0.05). Lactobacillus acidophilus inhibited establishing periodontic pathogens from red complex such as P. gingivalis and T. forsythia in a subgingival multispecies biofilm. Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Código de campo alterado Formatado: Inglês (Estados Unidos